Educational resources as predictors of effectiveness vocational and entrepreneurial skill acquisition programme in tertiary institutions in in Ogun state (2015)
Nigerians from various quarters have continued to advocate for inclusion of vocational and entrepreneurial skill acquisition as a means of ameliorating poverty, youth and graduate unemployment in the midst of a depressed economy. Some tertiary institutions in the Nigeria have risen to the occasion by establishing the centre for vocational and entrepreneurial skill acquisition, in response to the various calls for the need to do so. In order for the programme to be effective, there is need to consider the input variables that are in place for the programme to achieve its stated goals and objectives. The study therefore investigated some educational resources as predictors of the effectiveness of vocational and entrepreneurial skill acquisition programme in some tertiary institutions in Ogun state Nigeria. The subjects of the study included 534 trainees and 58 vocational skill tutors who were selected through the simple random sampling technique. Two questionnaires (Vocational Trainees' Perception Questionnaire [VTPQ] and Tutors' Perception Questionnaire [TPQ] were used for data collection, while multiple regression analysis was used for data analysis in the study. The findings of the study revealed that educational resources (human, financial and material resources) reliably predict the effectiveness of vocational and entrepreneurial skill acquisition programme. In the light this, it was recommended that the three educational resources should be adequately provided for and judiciously utilized to ensure the effectiveness of VOS programme. Furthermore, it was also recommended that a vocational trust fund organisation should be established to help supplement institutional financial inputs to cater for human and material resources needed for the effectiveness of the VOS programme.